Effect of Oftocord gel vs Actovegin on regenerative processes following mechanical trauma to the rabbit cornea - N.N. Moisieieva; A.K. Gulevsky; O.L. Gorina; Z.A. Seidaliieva (Ukrainian Society of Ophthalmologists, 2017)
Background: Mechanical damage to the cornea is followed by reduced collagen synthesis and imbalance in collagen ratio in the defect area, and by initiation of apoptosis in connective tissue cells, which may result in the transformation of granulation tissue into fibrous tissue. To prevent these alterations, corneal healing processes should be regulated with medications aimed at restoring corneal structure. Purpose: To compare the effect of Oftocord eye gel and Actovegin gel on changes in collagen I and collagen III synthesis and on apoptosis process in the rabbit cornea following mechanical corneal trauma. Materials and Methods: Thirty six Chinchilla rabbits were subjected to a standardized mechanical corneal damage. Thereafter, their corneal defect sites received one of the following treatments for 21 days: placebo gel with no active ingredient (Group 1), Oftocord gel containing a low-molecular weight fraction of human cord blood (HCBF) (Group 2), and Actovegin gel (Group 3). Enucleation for histological and histochemical studies was performed immediately after euthanasia at days 3, 7, 14 and 21. The composition of HCBF was studied and compared with that of Actovegin. Results: Oftocord gel applied to the site of corneal damage prevented the development of apoptosis and improved imbalance in the ratio of newly synthesized collagen I and III in the corneal defect area. The composition of HCBF versus Actovegin was studied to elucidate the mechanism of the effect of Oftocord gel on the metabolism of connective tissue. HCBF and Actovegin substantially differed from each other in composition both qualitatively and quantitatively, with the greatest differences observed in the content of glucuronic acid and of the glycoproteins exhibiting a dominating effect on the metabolism of the connective tissue. Conclusion: Applying Oftocord gel to the site of corneal damage promoted collagen I and III synthesis normalization, and reduction in the percentage of apoptotic cells in the cornea throughout the study. HCBF and Actovegin substantially differed from each other in composition both qualitatively and quantitatively.